Pengaruh Iklan Televisi terhadap Minat Beli Sabun Mandi pada Mahasiswa Fakultas Ekonomi Universitas Malikussaleh - Nurmala - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research is to identify the influence of television advertising to ward interest of buying soop at Economic Students is 97 respondents. With using purposive sampling. The data would be analyzed by using multiple regression linear. The result of research shows that R square 0,675, it meens 67,5% of independent variables there are X1 (Advertesing model), X2 (Slogan) and X2 (Repetation) explans the dependent variable y (interest of buying soop). Remain 32,5% is influenced by other variables.The result of F test as simultantly provid that independent variables influence the dependent variable as significantly, it shows with f test 67,477 > F table 2,71. And as partianlly is gotten T test for Independent variables (X1 = 3.550), (X2 = 6,923) and (X3 = 2,284). It means all of independent variables influence toward interest of buying soop by students of Economic Faculty, Malikussaleh University.Keywords: Advertising, Slogan, Repetitation.